Vibrational assisted conduction in a molecular wire. (22nd May 2017) - Pigeon, Simon; Fusco, Lorenzo; Chiara, Gabriele De; Paternostro, Mauro
Abstract: We present a detailed study of the conduction properties of a molecular wire where hopping processes between electronic sites are coupled to a vibrational mode of the molecule. The latter is sandwiched between two electronic leads at finite temperatures. We show that the electro-mechanical coupling can lead to a strong enhancement of the lead-to-lead conduction. Moreover, under suitable driving of the molecular vibrational mode, the device can act as a transistor passing sharply from enhanced conduction to short-circuit configuration.